PEMANFAATAN INTRANET SEBAGAI MEDIA KOMUNIKASI INTERNAL PUBLIC RELATIONS PT PERTAMINA (PERSERO) REFINERY UNIT (RU) II DUMAI, PROVINSI RIAU - Rahmawati, Nina; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Intranet is a network that is built on Internet technology in which there are webapplications and data communications technology. Intranet based LAN and using TCP / IP(Transmission Control Protocol / Internet Protocol) that enables a computer to send andreceive data based on the address of each. Thus, the intranet is very suitable for use by thePublic Relations (PR) PT. Pertamina RU II Dumai as the company's internalcommunications media.The purpose of this research is to 1). Knowing the effectiveness of PR in usingintranet, 2). Knowing how to deliver information from the company's internal PR, 3).Knowing the response of employees in the use of the intranet.This study uses descriptive qualitative approach Organizing Theory or Theory ofInformation and Organization Two way assymetrical Model (Model Asymmetric Two-Way).Data collection techniques using nonparticipant observation, in-depth interviews, anddocumentation. Informants selected by purposive sampling technique and technique ofAccidental, informants consisted of Public Relations Section Head, Chief Editor of Data &Media Publications Officer and employees of Pertamina RU II Dumai.From the results of this study, researchers concluded that: 1). PR publishing companypolicies and information well on the intranet, seen from the enthusiasm of employees inresponding it 2). PR plays a major role in publicizing information via the intranet, so that thedelivery of information is quite prevalent in the corporate environment. 3). The response ofemployees in the use of the intranet is good enough, because the employees are veryenthusiastic in response to any renewal of existing on the company intranet. currentlyexisting within the intranet Idea Generation in sub site that serves to accommodate all theaspirations, ideas, comments and so on, but there is still not a direct two-way communicationin the intranet menu.Keyword : Public Relations, Internal Communication, Media Public Relations,Technology, Intranet.